2018
DOI: 10.1159/000490952
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Atopy following Mass Drug Administration with Albendazole: A Study in School Children on Flores Island, Indonesia

Abstract: Background: In many rural areas of tropical countries such as Indonesia, the prevalence of soil-transmitted helminths (STH) infections remains high. At the same time, the burden of allergic disorders in such rural areas is reported to be low and inversely associated with helminth infections. To reduce the morbidity and transmission of helminth infections, the world health organization recommends preventive treatment of school children by providing mass drug administration (MDA) with albendazole. Here, we had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Deworming studies have shown that monthly anthelmintic treatment of children for 18 months caused an increase in the prevalence of skin test reactivity to HDMs in Venezuela113 and that treatment with praziquantel and mebendazole every 3 months for 30-months was associated with an increase in the incidence of skin reactivity to HDMs in Gabon 114. A more recent study also confirmed that positive skin test results to HDMs increased from 18.7% to 32.7% after albendazole treatment in Flores Indonesia 115. Interestingly, a 2-fold increase in allergen sensitization was observed in Ethiopian immigrants after 1 year in Israel, particularly for HDMs 116…”
Section: Factors Adjuvating the Ige Response To Hdmmentioning
confidence: 90%
“…Deworming studies have shown that monthly anthelmintic treatment of children for 18 months caused an increase in the prevalence of skin test reactivity to HDMs in Venezuela113 and that treatment with praziquantel and mebendazole every 3 months for 30-months was associated with an increase in the incidence of skin reactivity to HDMs in Gabon 114. A more recent study also confirmed that positive skin test results to HDMs increased from 18.7% to 32.7% after albendazole treatment in Flores Indonesia 115. Interestingly, a 2-fold increase in allergen sensitization was observed in Ethiopian immigrants after 1 year in Israel, particularly for HDMs 116…”
Section: Factors Adjuvating the Ige Response To Hdmmentioning
confidence: 90%
“…Several epidemiology studies have shown inverse associations of chronic parasitic worm infections with allergy and atopy in regions of high prevalence of such infections ( van den Biggelaar et al., 2004 ; Leonardi-Bee et al., 2006 ; Mpairwe et al., 2008 ; Rujeni et al., 2012 ; Webb et al., 2016 ). Other studies in schoolchildren have produced conflicting results with regard to the effects of deworming on SPT responses ( van den Biggelaar et al., 2004 ; Cooper et al., 2006 ) A study in Indonesia found that SPT reactivity increased after 1 year of albendazole treatment, in Gabon SPT reactivity was significantly reduced in children infected with S.haematobium and in Ecuador, albendazole treatment had no effect on the prevalence of SPT reactivity ( Lynch et al., 1993 ; van den Biggelaar et al., 2000 ; Cooper et al., 2006 ; Staal et al., 2018 ). In this study, when we examined the effects of S.haematobium infection status and SPT status on NMDS scores our results showed that SPT status had a significant effect on NMDS scores for NMDS3 (IgA) for S.cerevisiae with SPT-negative individuals having significantly higher IgA response compared to SPT-positive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that there is no link between helminthiasis and the onset of AD. Other studies have shown that helminthiasis is a protective factor against allergic diseases including AD [8,[25][26][27]. According to the authors of the hygiene theory, the presence of helminthiasis induces the secretion of anti-inflammatory cytokines and/or an increased response of suppressor T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors of the hygiene theory, the presence of helminthiasis induces the secretion of anti-inflammatory cytokines and/or an increased response of suppressor T lymphocytes. e reduction of infectious diseases through vaccination and deworming leads to a reorientation of the immune system towards the 2 mechanism and so an increased sensitization to allergens [15,19,[25][26][27][28][29]. e hygiene theory also supports the fact that the lack of stimulation of the body by microbes is a risk factor for the onset of atopic diseases.…”
Section: Discussionmentioning
confidence: 99%